THE IMPROVEMENT OF THE RELIABILITY OF THE SYSTEM SPEED AUTOMATIC TRIGGER ON THE ELECTRIC ER2R, ER2T AND EPL2T - Visyn, N. H.; Vlasenko, B. T.; Sokolov, O. O. (Science and Transport Progress, 2005)
The article examines transitional processes in the power circuit of tractive motors and their influence on the work of grading automatic starting of EMU trains ER2R, ER2Т and EPL2Т. Recommendations have been developed for increasing reliability of operations of multiple-unit rolling stock.